Vacuolar Protein-Sorting Receptor MoVps13 Regulates Conidiation and Pathogenicity in Rice Blast Fungus Magnaporthe oryzae - Xueming Zhu; Lin Li; Jiaoyu Wang; Lili Zhao; Huanbin Shi; Jiandong Bao; Zhenzhu Su; Xiaohong Liu; Fucheng Lin (Journal of Fungi, 2021)
Magnaporthe oryzae (synonym Pyricularia oryzae) is a filamentous fungal pathogen that causes major yield losses in cultivated rice worldwide. However, the mechanisms of infection of M. oryzae are not well characterized. The VPS13 proteins play vital roles in various biological processes in many eukaryotic organisms, including in the organization of actin cytoskeleton, vesicle trafficking, mitochondrial fusion, and phagocytosis. Nevertheless, the function of the Vps13 protein in plant pathogenic fungi has not been explored. Here, we analysed the biological functions of the Vps13 protein in the development and pathogenicity of M. oryzae. Deletion mutants of MoVps13 significantly reduced the conidiation and decreased the rate of fungal infection on hosts. Moreover, the loss of MoVps13 resulted in defective cell wall integrity (CWI) and plasma membrane (PM) homeostasis when treated with chemicals for inducing cell wall stress (200 mg/mL Congo Red or 0.005% SDS) and sphingolipid synthesis inhibitors (2 μM myriocin or 2 μM amphotericin B). This indicated that MoVps13 is also involved in cell wall synthesis and sphingolipid synthesis. Through immunoblotting, autophagic flux detection, co-localization, and chemical drug sensitivity assays, we confirmed the involvement of Movps13 in ER-phagy and the response to ER stress. Additionally, we generated the C-terminal structure of MoVps13 with high accuracy using the alphaflod2 database. Our experimental evidence indicates that MoVps13 is an important virulence factor that regulates the pathogenicity of M. oryzae by controlling CWI, lipid metabolism and the ER-phagy pathway. These results have expanded our knowledge about pathogenic fungi and will help exploration for novel therapeutic strategies against the rice blast fungus.